Another inconsistency in the pedigree of the Oak Ridge wild types of Neurospora crassa - Olivera Gavric; Anthony Griffiths (Fungal Genetics Reports, 2004)
A multiple-site molecular dimorphism for the gene for phospholipase C has no known evolutionary basis, yet reveals that Oak Ridge wild types cannot have originated as described in the current best pedigree.